Development of a new jet fuel surrogate and its associated reaction mechanism coupled with a multistep soot model for diesel engine combustion. (15th October 2018) - Yu, Wenbin; Tay, Kunlin; Zhao, Feiyang; Yang, Wenming; Li, Han; Xu, Hongpeng
Highlights: A new jet fuel surrogate was developed by emulating real jet fuel properties. A jet fuel skeletal reaction mechanism coupled with a multistep soot model was developed. Mechanism validations of ignition delay times, species concentrations and laminar flame speed were done. Validations in a constant volume chamber and an engine showed the reasonableness of this mechanism for application. Abstract: A new jet fuel surrogate was developed in this work by emulating real jet fuel properties including physical, gas phase chemical properties and threshold sooting index (TSI). An intelligent optimization methodology was proposed to calculate the species composition that inherently satisfies both the physical and chemical characteristics as well as sooting tendency. Eight properties were selected as the target properties for the jet fuel surrogate development, including liquid density, viscosity, surface tension, cetane number (CN), hydrogen carbon (H/C) ratio, molecular weight (MW), lower heating value (LHV) and TSI. As a result, the CN, H/C ratio, LHV, TSI and density of the new jet fuel surrogate are reproduced excellently with very little deviations within 3%. The averaged deviation of viscosity is −6.318% and the deviations of MW is 9.776%. As the highest deviation among all properties, the averaged deviation of surface tension is 11.76%. Based on the newly developed jet fuel surrogate, a skeletal jet fuel surrogate mechanism with 5 components including decalin, n -dodecane, iso -cetane, iso -octane and toluene was developed. The skeletal jet fuel surrogate mechanism was significantly compacted into 74 species and 189 reactions by describing the chemistries for the oxidation of large molecules C4 –Cn and small H2 /CO/C1 molecules respectively, which makes it practical to be used for 3-D engine combustion simulations. The validations of ignition delay times present reasonable agreement between experiment and predictions over a wide range of equivalence ratios (0.5–2.0) and pressures (8–30 atm), except for a shift of negative temperature coefficient (NTC) region towards higher temperatures at Φ = 1.5, 20 atm: in the simulation the NTC region is from 830 K to 950 K while in the experiment the NTC region is from 740 K to 890 K. The predicted species concentrations can reproduce the trend of the experimental data, especially for O2, CO and CO2 . The simulated laminar flame speed at 400 K and 470 K are with absolute averaged deviations of 3.5% and 4.06% respectively. The constant volume spray and combustion validations are reasonably good. In the engine combustion validations, a multistep soot model was embedded into the new jet fuel surrogate mechanism. The predicted in-cylinder pressure can reproduce the experimental data, expect for small deviations after the peak pressure (the averaged deviation is around 6.2% after the peak pressure). The embedded soot model can well reproduce the trend of the experimental data. It can be concluded that this new jet fuel surrogate mechanism is compact and robust for the utilization in diesel engine combustion simulation.